Intensidade luminosa aplicada na recria, desempenho e produção de ovos de codornas japonesas - Makiyama, Letícia (2016)
The present work was conducted with the objective of verifying the influence of light intensity in continuous illumination programs of 12 hours/day, for Japanese quail in the rearing phase (15 to 35 days of age), over performance, viscera development, body growth and, posteriorly, egg production. We used 1554 female Japanese quail, distributed into six treatments and seven replicates of 37 birds. During the rearing phase, the birds were lodged in shed with light isolation. From the14 th day of age, the birds were reared in the experimental treatments: 5, 10, 20, 30, 40 and 50 lux in continuous photoperiod of 12 hours per day. At 35 days of age, the birds were weighed and transferred to laying installations with identified plots. The light intensities exerted influence only over performance and growth in the rearing phase. The intensity of five lux, in 12 daily hours continuous illumination programs can be used in the rearing phase, for it maximizes body weight at maturity age and improves food conversion without influencing viscera development, beginning of the laying phase and productive performance during laying.